Environmental Education and English Language: in search of a sustainable and liberating school (Research, Society and Development, 2021)
This literature review article is the result of an academic activity of the Master in Professional and Technological Education (PROFEPT) of the Instituto Federal do Piauí (IFPI) in progress. Contemporary foreign language teaching has been shown to be of great importance for the development of academic and professional training in a contemporary sociocultural dynamic. Thus, this article sought to discuss the following epistemological aspects, namely: professional education and environmental education: conceptions and interrelationships; applicability of the textbook as teaching material in English language teaching contextualized in English language classes in the High school Technical Course in Environment. This academic-scientific study in terms of objective is characterized as basic research with a qualitative approach and consists of a systematic literature review. From this scientific-research, the importance of the need to integrate content and didactic materials that articulate professional training and propaedeutic training was evidenced, and that enables the student to develop creative skills of reflection and perception to be incorporated in their citizenship training and socio-environmental responsibility. It was also observed the need to build a teaching practice that addresses the theme of the environment, considering the inseparability between education and social practice to face issues related to socio-environmental issues. The aim of this study is to awaken the critical view of the professors to teaching intertwined between the disciplines, propaedeutics, English and techniques of the Environmental Technical Course.